Shortest Route Search for Tourist Attractions in Bandung Using Dijkstra's Algorithm - SY., Yuliani (International Journal of Psychosocial Rehabilitation, 2020)
Dijkstra's algorithm is one of the algorithms that can solve the problem of finding the shortest route which is a problem in graph theory. Implementation of the system that we use will result in a website application that uses the Javascript programming language. This system uses the Dijkstra algorithm which is very useful for visitors because tourists can find the shortest route that can be taken to and from a tourist destination in the area of Bandung that you want to visit using this system. With the research of the shortest route using the Djikstra algorithm to find the fastest route of tourist attractions in the city of Bandung, the tourists can add information about the fastest route and finally the tourists can choose the best route that can streamline all costs and find out all the information on tourist objects in This city of Bandung.